AFFORDANCES DA COIL: Análise de uma experiência entre UFES e UAH - Hildeblando Júnior, Carlos Alberto (2019)
The main objective of this research study is to reflect about the affordances of the Collaborative Online International Learning (COIL) approach to support the internationalization of higher education. More specifically, this study seeks to analyze the af